"Finger coral-like" ceramic fiber aerogels with enhanced high-temperature thermal insulation, anti-oxidation, and mechanical performance. (7th July 2022) - Wang, Jianyu; Li, Hongyan; Liu, Hongli; Lu, Le; Wang, Tao
Abstract: Ceramic fiber aerogels are widely used in high temperature insulation. Thermal insulation under extreme conditions requires materials that can withstand sharp thermal shocks and extended high-temperature exposure. However, the oxidation resistance of traditional ceramic aerogels under a high temperature environment(above 1000 °C) is significantly reduced. Moreover, the strength degradation and structural collapse easily occurred, restricting their application. In this study, "Finger Coral" ceramic fibers aerogels were obtained using precursor infiltration pyrolysis (PIP) and electrospinning technology. The chemical composition, morphology, thermal insulation, mechanical properties and isothermal oxidation properties of SiCBN/SiC/disilicates nanoparticles (IP) ceramic aerogels were tested. The experimental results showed that the aerogel exhibited excellent mechanical and antioxidant properties over a wide range of temperatures. SiCBN/SiC/IP aerogel with a thickness of 2cm can achieve the heat insulation effect of the hot surface temperature from 1600 to 75 °C, and the thermal conductivity at 1600 °C was only 0.036 W·m −1 ·K −1 . After 12 h of cyclic isothermal oxidation, the weight gain was only 5.17%. The material is expected to be used as a thermal insulation material in the hypersonic vehicles. Graphical abstract: Image 1